Saúde bucal em gestantes e crianças de 0 a 5 anos: estratégias para promoção de saúde - Ana Paula Vieira Perdigão Jardim (2021)
Children under five years have a prevalence of caries between 30 and 50% in Brazil and worldwide, with almost all of this percentage represented by untreated dental caries. The health and development of children, especially those under two years of age, have important consequences for their adult lives. Considering that children in this age group need to be cared for, this research aimed to understand the perception of health and education professionals and parents or guardians about the oral health of children aged 0 to 5 years, in a municipality in the metropolitan region of Belo Horizon. Knowing what health professionals and those responsible for children in the family think about care and oral health, is one of the fundamental components for the development of more effective action strategies to deal with problems for this age group. For this purpose, the study used a qualitative approach and, as an instrument for data collection, the focus group, carried out with two groups: one with the guardians and the other with the professionals. Content analysis was carried out according to Graneheim and Lundman, taking as a theoretical reference the guidelines of the National Oral Health Policy for this age group. Three themes common to both groups were identified: the role of the service, the family and the school in the production of health. Participants considered that the family is responsible for the care of the child, together with the school and health services, and that this care should start from conception, with the pregnant woman. These results will be important for health professionals, society and for the implementation of protocols in services.